2013
DOI: 10.4103/0973-1482.110358
|View full text |Cite
|
Sign up to set email alerts
|

Morphological profile and receptor status in breast carcinoma: An institutional study

Abstract: Breast carcinoma in our population presents at younger age than Western population. Our results showed very high proportion of triple-negative breast cancers. The tumor size and grade is related to expression of only ER. The findings suggest that women in our population more often have histologically aggressive breast carcinoma at young age, likely to be less susceptible to conventional hormonal and targeted antibody treatment. Detecting and treating this increasing important cause of mortality will be an enor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
22
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 15 publications
15
22
2
Order By: Relevance
“…Alike some other studies, the hormone receptor status in the present study significantly correlated with the histological grade of breast tumors (Sofi et al, 2012;Shet et al, 2009;Ambroise et al, 2011). Similar to a regional study, lymphovascular space invasion was seen in less than 20% of the patients (Rao et al, 2013). Presence of histologic tumor necrosis has been found to be higher in Indian studies (Rao et al, 2013).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Alike some other studies, the hormone receptor status in the present study significantly correlated with the histological grade of breast tumors (Sofi et al, 2012;Shet et al, 2009;Ambroise et al, 2011). Similar to a regional study, lymphovascular space invasion was seen in less than 20% of the patients (Rao et al, 2013). Presence of histologic tumor necrosis has been found to be higher in Indian studies (Rao et al, 2013).…”
Section: Discussionsupporting
confidence: 62%
“…Similar to a regional study, lymphovascular space invasion was seen in less than 20% of the patients (Rao et al, 2013). Presence of histologic tumor necrosis has been found to be higher in Indian studies (Rao et al, 2013).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Thus, higher the tumor grade, more the unfavourable receptor expression and therefore, worse the prognosis. This is also in agreement with other studies which state that tumor histologic grade is an important determinant of hormone receptor status [11][12][13][14][15]. Tatjana Ivković-Kapicl et al in corroboration with our study, observed that highergrade tumors were more likely to demonstrate HER2/neu amplification than lower grade ductal carcinomas [16].…”
Section: Discussionsupporting
confidence: 82%
“…(Table 1) According to recurrence, 66 patients reported the occurrence of recurrence representing 19.7% of total number of study patients; with 29 cases of loco-regional recurrence and 37 cases with distant relapse; while 269 patients had no relapse till the time of study representing 80.3% of total study patients which is statistically significant (p=0.000). (Figure 3 (47)(48)(49) As regards to the size of the tumors in our study, T2 tumors (2-5 cm in size) were the commonest presenting tumors in all molecular subtypes where they represented 60.5% of total number of patients, T1 (less than 2 cm) represented 24.0% of patients and T3 (more than 5 cm) represented 15.5% of total number of patients. Rakha EA et al conducted a study on 2,219 cases.…”
Section: Figure (2)mentioning
confidence: 74%